Monitoring 3rd of March 2011 Dust Storm in Iraq Using Meteosat 9 Images - Kahdom, Azhar; Abdul Ali, Abdul kareem (Iraqi Journal of Science, 2024)
Dust storms phenomenon were studied qualitatively in this research with the aides of Meteosat-9 images that has been used for monitoring the path and coverage of the dust storm. The monitoring of dust storm movement were done by using true colour composite image supplied by Europe’s meteorological satellite agency EUMETSAT. The Image processing techniques are applied by using ERDAS 8.4 package, where in the first step the images are corrected by Geometric Correction technique for the purpose of obtaining images from which to read the real geographical coordinates. Dust storm coverage area was calculated by using the supervise classification mechanism, as well as been identifying and tracking the change of dust cloud during different stages of dust storm period. The speed of dust storm were calculated by identifying the front pattern of the dust cloud and found to be (37.62) km / h.